2013
DOI: 10.1007/s12291-013-0383-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Serum Calcium and Phosphorus in Pulmonary Tuberculosis Patients Before, During and After Chemotherapy

Abstract: Our study was aimed to assess the levels of serum calcium and phosphorus in pulmonary tuberculosis patients. Blood samples were collected from 40 patients with pulmonary tuberculosis before treatment (PTB-0), at the end of 2 months of intensive phase of treatment (PTB-2) and after 6 months of treatment (PTB-6). Age and weight matched normal healthy volunteers (n = 37) served as normal controls. Serum was analyzed for calcium and phosphorus. Serum calcium significantly decreased to hypocalcemic levels and serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 10 publications
1
19
2
Order By: Relevance
“…In our study, the PTB subjects were just diagnosed with tuberculosis and hence immunocompromised. We also found decreased serum phosphate in these animals, the details of which we have discussed in an earlier report [3,4,[18][19][20]. The proinflammatory milieu could have reduced production of erythropoietin, suppressed response of bone marrow to erythropoietin, and altered iron metabolism, which in turn could have impaired erythropoiesis [17].…”
Section: Discussionsupporting
confidence: 65%
“…In our study, the PTB subjects were just diagnosed with tuberculosis and hence immunocompromised. We also found decreased serum phosphate in these animals, the details of which we have discussed in an earlier report [3,4,[18][19][20]. The proinflammatory milieu could have reduced production of erythropoietin, suppressed response of bone marrow to erythropoietin, and altered iron metabolism, which in turn could have impaired erythropoiesis [17].…”
Section: Discussionsupporting
confidence: 65%
“…Hypophosphatemia is a common co-morbidity in critically ill patients including sepsis ( 11 ), often leading to increased mortality, prolonged duration of MV and intensive care unit (ICU) stay ( 11 , 12 ). Some reports have suggested an association between respiratory illness and hypophosphatemia ( 13 , 14 ), the latter of which significantly contributed to failure of weaning ( 15 ) and according to Haider et al ( 16 ), was an independent risk factor for mortality in critically ill patients. It was reported that the 24-h plasma phosphate level in some ICU patients after admission, especially those with respiratory failure, decreased to the reduced renal threshold of phosphate concentration ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…The mean serum Ca levels were 7.2 mg/dL and 9.4 mg/dL in the test and control groups, respectively; statistically the difference was not significant between the groups (P > 0.05). In the test group, 28% (14), 34% (17), 16% (8) and 22% (11) participants were graded as scanty, 1+. 2+ and 3+, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Several investigators studied on level of serum (Ca) among the TB patients [16][17][18][19]. But, we cannot find studies on correlation between levels of serum Ca and smear grading.…”
Section: Introductionmentioning
confidence: 99%